Adherence to Norms of Conduct, Public Trust, and Service Delivery of DENR-CENRO - Suarez, Aiza (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examines the relationship between government employees’ adherence to norms of conduct, public trust, and satisfaction with service delivery in the Department of Environment and Natural Resources–Community Environment and Natural Resources Office (DENR-CENRO) in Tagbilaran, Bohol. Anchored on Social Contract Theory, Social Norms Theory, Principal-Agent Theory, Trust Theory, and Theory of Justice, the study explains how ethical behavior influences governance outcomes. A quantitative descriptive-correlational research design was employed, involving 517 respondents composed of 133 employees selected through stratified random sampling and 384 clients selected through convenience sampling. Data were gathered using a structured questionnaire and analyzed using weighted mean, Spearman Rank Correlation, and Mann-Whitney tests. Findings reveal a very high level of adherence to norms of conduct, public trust, and satisfaction with service delivery, although employees consistently reported higher perceptions than clients. Responsiveness and timeliness were identified as the lowest-rated dimensions across variables. The results further show strong, statistically significant relationships among adherence to norms of conduct, public trust, and satisfaction with service delivery, indicating that these factors are interconnected and mutually reinforcing. The study concludes that while ethical standards are strongly practiced, improvements in responsiveness and timeliness are necessary to align institutional performance with client expectations. Recommendations focus on enhancing service delivery processes, strengthening client-centered practices, and addressing perceptual gaps between employees and clients. The study supports SDG 16 (Peace, Justice, and Strong Institutions) by promoting transparency and accountability, as well as SDG 8 (Decent Work and Economic Growth) through improved public service efficiency. Its sustainability impact lies in strengthening institutional governance, enhancing public trust, and promoting efficient and citizen-centered service delivery within government systems.